2020
DOI: 10.1002/1348-9585.12147
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence occupational physicians’ decision to issue an employer warning in Japan

Abstract: Objectives To elucidate the factors that influence occupational physicians’ decision to issue an employer warning. Methods The interview was conducted with 10 Japan Society for Occupational Health certified occupational physicians (COPs) and certified senior occupational physicians (CSOPs) to create nine fictive scenarios in which an occupational physician may need to consider issuing a warning. Sixteen CSOPs assessed the seriousness of the problem in each of nine scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, the companies responded as if a formal recommendation had been submitted. In a survey about OHPs' formal recommendations, it was found that these were often issued when the OHP's opinions or instructions had been neglected and the OHP needed to take further action and/or there had clearly been a violation of the legislation 9,10) . In this case study, the background to the OHP notifying the company that they might issue a formal recommendation included: (i) the significant risk of damage to employees' health; (ii) the violation of laws about working environment management; and (iii) the company's agreement to receive a formal recommendation.…”
Section: Implicationmentioning
confidence: 99%
“…However, the companies responded as if a formal recommendation had been submitted. In a survey about OHPs' formal recommendations, it was found that these were often issued when the OHP's opinions or instructions had been neglected and the OHP needed to take further action and/or there had clearly been a violation of the legislation 9,10) . In this case study, the background to the OHP notifying the company that they might issue a formal recommendation included: (i) the significant risk of damage to employees' health; (ii) the violation of laws about working environment management; and (iii) the company's agreement to receive a formal recommendation.…”
Section: Implicationmentioning
confidence: 99%